Seizure Outcome after Surgical Treatment for Temporal Lobe Epilepsy with Hippocampal Sclerosis - Kumpanont, Tanatkan; Srikijvilaikul, Teeradej (Thai Journal of Neurological Surgery, 2025)
Objective: To study seizure outcomes in patients with temporal lobe epilepsy (TLE) with hippocampal sclerosis (HS) and predictive factors associated with seizure outcome. Material and Methods: One hundred and forty-seven patients with drug-resistance temporal lobe epilepsy with hippocampal sclerosis were retrospectively reviewed at Neurological Institute of Thailand between 2011 and 2021. All patients underwent temporal lobectomy and had pathologically proven hippocampal sclerosis. A minimum follow-up period was two years and seizure outcomes were classified as being seizure free and not seizure free using Engel’s classification. Results: A total of 109 patients were included in the study, there were 47 males and 62 females. The median follow-up duration was 4 years. Long-term seizure freedom at 2 years was 86.2% and at 5 years was 85.1%. Overall, 93 (85.3%) patients were seizure free (Engel I) at their last follow-up. Ninetyfour (86.2%) patients were seizure free at a minimum of two years after surgery. Thirty-four patients were able to discontinue anti-seizure medication. There was 14% morbidity rate with no mortality. No predictive factors were found associated with seizure outcome in this study. Conclusion: Temporal lobectomy is effective in drug-resistant temporal lobe epilepsy with hippocampal sclerosis. Favorable seizure free outcomes at least two years can be achieved. However, there are no predictive factors associated with seizure outcome in this study.